Breast surface coordinate variation analysis caused by round shape tumor with fringe projection profilometry - Wan Mokhdzani Wan Nor Haimi; Rajendaran Vairavan; Zaliman Sauli; Vithyacharan Retnasamy; Hafiz Aziz; Hasnizah Aris; Mukhzeer Mohamad Shahimin (2018)
Breast cancer is one of the fatal diseases and is one of the leading causes of death among women. Early screening for breast cancer is highly needed among women. Monitoring of the disease is also extremely vital for determining the best possible method of treatment. One of the most common symptoms of breast cancer is the breast surface change caused by the tumor within the breast. Shapes of the tumor vary among the patients, and some of the standard shapes of the tumor are round, oval, irregular, spiculated and microlobulated. Current common imaging modalities of diagnosing for breast tumor is the Magnetic Resonance Imaging (MRI), ultrasound and mammography. The current imaging modalities have been known to diagnose the disease but also has its limitations due to exposure concerns. In this work, the changes of breast surface are analyzed using a proposed fringe projection imaging modality. Surface changes of the breast were analyzed with the presence of a round shape tumor varied from 0.5 cm to 2 cm. The fringe projection profilometry system has successfully demonstrated its ability in detecting the pixel coordinate changes of the breast surface caused by the size variation of the tumor.